2022
DOI: 10.1523/jneurosci.0936-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Release in the Prefrontal Cortex Excites Fast-Spiking Interneurons while GABA Released from the Same Axons Inhibits Pyramidal Cells

Abstract: We studied how histamine and GABA release from axons originating from the hypothalamic tuberomammillary nucleus (TMN) and projecting to the prefrontal cortex (PFC) influence circuit processing. We optostimulated histamine/GABA from genetically defined TMN axons that express the histidine decarboxylase gene (TMNHDCaxons). Whole-cell recordings from PFC neurons in layer 2/3 of prelimbic, anterior cingulate, and infralimbic regions were used to monitor excitability before and after optostimulated histamine/GABA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The neuromodulator histamine is synthesized by neurons located in the tuberomammillary nucleus (TMN) of the hypothalamus which send wide-spread axonal projections and release histamine throughout the central nervous system (Haas & Panula, 2003;Haas et al, 2008;Lin et al, 2023). Although classically assumed to mainly regulate the sleep-wake cycle, the histaminergic system is now thought to have many more diverse physiological roles in a multitude of brain regions and stages of life (Schwartz et al, 1991;Takahashi et al, 2006;Panula et al, 2014;Han et al, 2020;Lucaci et al, 2023), and has been shown to be dysfunctional in various neurological and neurodevelopmental disorders (Ercan-Sencicek, 2010; Shan et al, 2015;Carthy & Ellender, 2021;Xu et al, 2022;Ma et al, 2023). For example, Tourette's syndrome (TS) is an earlyonset disorder that is characterized by involuntary motor and vocal tics often comorbid with obsessive-compulsive disorder (OCD) and depression (Robertson et al, 2017) and parallel findings in patients and mouse models suggest that a disruption of the histaminergic system and reduced levels of histamine can be part of the etiology (Ercan-Sencicek, 2010;Fernandez et al, 2012;Karagiannidis et al, 2013;Baldan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The neuromodulator histamine is synthesized by neurons located in the tuberomammillary nucleus (TMN) of the hypothalamus which send wide-spread axonal projections and release histamine throughout the central nervous system (Haas & Panula, 2003;Haas et al, 2008;Lin et al, 2023). Although classically assumed to mainly regulate the sleep-wake cycle, the histaminergic system is now thought to have many more diverse physiological roles in a multitude of brain regions and stages of life (Schwartz et al, 1991;Takahashi et al, 2006;Panula et al, 2014;Han et al, 2020;Lucaci et al, 2023), and has been shown to be dysfunctional in various neurological and neurodevelopmental disorders (Ercan-Sencicek, 2010; Shan et al, 2015;Carthy & Ellender, 2021;Xu et al, 2022;Ma et al, 2023). For example, Tourette's syndrome (TS) is an earlyonset disorder that is characterized by involuntary motor and vocal tics often comorbid with obsessive-compulsive disorder (OCD) and depression (Robertson et al, 2017) and parallel findings in patients and mouse models suggest that a disruption of the histaminergic system and reduced levels of histamine can be part of the etiology (Ercan-Sencicek, 2010;Fernandez et al, 2012;Karagiannidis et al, 2013;Baldan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%